(untitled) (International Journal of Engineering and Computer Science, 2014)
The implementation of a modern seismic network involves many different research and technological aspects related to the development of sophisticated data management and processing. The communication systems need to rapidly generate useful, robust, and secure alert notifications. Here we provide a general technical and seismological overview of ISNet’s complex architecture and implementation. The implementation of a modern seismic network involves many different research and technological aspects related to the development of sophisticated data management and processing. The communication systems need to rapidly generate useful, robust, and secure alert notifications. Here we provide a general technical and seismological overview of ISNet’s complex architecture and implementation twitter has received much attention recently. An important characteristic of twitter is its real-time nature. investigate the real-time interaction of events such as earthquakes in Twitter and propose an algorithm to monitor tweets and to detect a target event. To detect a target event, devise a classifier of tweets based on features such as the keywords in a tweet, the number of words, and their context. Subsequently, produce a probabilistic spatiotemporal model for the target event that can find the center of the event location.